Pengembangan Media Promosi Potensi Desa Oepuah Dengan Menggunakan Metode Waterfall - Krisantus Jumarto Tey Seran; Victoria Nova Naiheli (Department of Information Technology, Universitas Timor, Indonesia, 2021)
Abstract - Oepuah Village is one of the villages that has a lot of local potential to be promoted such as agricultural products, livestock, fisheries, and local wisdom of the local community. The problems faced today is the information about the local potential in the village Oepuah date cannot be accessed by the public for the delivery of information can only be obtained when come to the local village office. Seeing this problem, it is necessary to build a promotional website that can be used to help introduce the local potential of this area to the outside world online. In building this website, use the waterfall method is a method that provides a workflow approach to software life systematically. Results from this study may help provide convenience in providing complete information about the surrounding countryside as well as to promote the potential of a very menononjolkan featured local agricultural potential, the potential for animal husbandry, fisheries and cultural potential that can be known by the public.